Effects of trade and FDI on economic growth in Africa: an empirical investigation. Issue 2 (3rd April 2017) - Sakyi, Daniel; Egyir, John
Abstract: The Bhagwati hypothesis predicts a growth enhancing effects of trade (exports) and foreign direct investment (FDI) interaction. This paper tests the validity of the Bhagwati hypothesis by investigating the extent to which the interaction of trade (exports) and FDI has had an impact on economic growth for a sample of 45 African countries over the period 1990–2014. To do so, we estimate an augmented endogenous growth model with the aid of a dynamic system generalised method of moment (GMM) estimation technique, which adequately cope with potential endogeneity issues. The findings reveal support for the Bhagwati hypothesis and provide vital information for policy formulation aimed at promoting more credible export-promotion strategies and channelling of FDI into export-oriented sectors in long-term development strategies in African countries.